STUDI LITERATUR: PERAN SENYAWA BIOAKTIF WORTEL DALAM MENURUNKAN RISIKO XEROPHTHALMIA DAN RABUN SENJA - Ekarniman Gulo; Tria Wulandari; Ida Duma Riris; Salwa Hakimah Defari; Adna Aprilia Waruwu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Vitamin A deficiency can cause health problems that affect vision, such as night blindness and xerophthalmia. One way to prevent this disease is by consuming foods rich in provitamin A, especially β-carotene. This study aims to discuss the role of bioactive compounds found in carrots (Daucus carota L.) in reducing the risk of xerophthalmia and night blindness by conducting a literature review, namely by analyzing various related scientific articles. Research shows that carrots are a fairly high source of β-carotene, which can be converted into vitamin A according to the body’s needs. Vitamin A can also play an important role in helping the formation of rhodopsin, which is needed for clear vision in dim light conditions. In addition, this vitamin is also important for maintaining the integrity and function of the eye’s epithelial tissue. Furthermore, β-carotene also has the ability to protect eye cells from damage caused by oxidation due to its antioxidant properties. Consuming carrots can help increase vitamin A levels in the body, prevent night blindness and xerophthalmia, and provide benefits for general eye health. Nutrition education, particularly the importance of consuming foods containing vitamin A, is needed to raise public awareness and prevent vitamin A deficiency.